Global Finance and Business Sustainability in Brazil - Madi, Maria Alejandra Caporale (Journal of Reviews on Global Economics, 2013)
The recent Brazilian policy agenda has not been able to improve the business environment in order to increase the resiliency of micro and small enterprises over time. Business sustainability is particularly relevant in a global scenario where, among the major challenges, the crisis has restated the menace of a deep depression while livelihood conditions turned out to be subordinated to the bailout of the domestic financial systems.As a matter of fact, the current global financial architecture has seriously affected the pace of long-run investment and threatened the survival of micro and small enterprises. Taking into account this background, our main concern is to reflect on how entrepreneurship sustainability is influenced by finance in contemporary Brazil - mainly after the 2008 global crisis.